Enhancing M-Learning System Using Cloud Computing - Sharmila; Jebaseeli, Nisha (International Journal of Computer Sciences and Engineering, 2025)
The main aim of this paper is to study the concept of M-Learning system enhancement using Cloud computing technologies. M-Learning system can be enhanced by the new Cloud computing technologies. M-Learning system is flexible and it has some advantages than the traditional educational system. Furthermore, MCC-Mobile Cloud computing is the new technology which integrates Mobile Computing and Cloud computing which has many advantages than M-Learning. Storage space, processing speed and other services from the cloud environment are utilized in MCC to enhance the networked collaborative learning process. This paper discusses the concept of Mobile Learning and Cloud computing, Cloud architecture and its benefits. It also discusses the benefit of Cloud computing in Mobile Learning. Through Cloud computing and Cloud environment the learner’s mobile device is able to receive unbroken transmission signals which enhances the barrier free communication process. Mobile Cloud computing modifies the teacher’s role from lecturing to facilitating the learning process i.e. student centered learning.